The relevance of environment vs. composition on dissolved organic matter degradation in freshwaters - Núria Catalán; Ada Pastor; Carles M. Borrego; Joan Pere Casas‐Ruiz; Jeffrey A. Hawkes; Carmen Gutiérrez; Daniel von Schiller; Rafael Marcé (Limnology and Oceanography, 2021)
Dissolved organic matter (DOM) composition exerts a direct control on its degradation and subsequent persistence in aquatic ecosystems. Yet, under certain conditions, the degradation patterns of DOM cannot be solely explained by its composition, highlighting the relevance of environmental conditions for DOM degradation. Here, we experimentally assessed the relative influence of composition vs. environment on DOM degradation by performing degradation bioassays using three contrasting DOM sources inoculated with a standardized bacterial inoculum under five distinct environments. The DOM degradation kinetics modeled using reactivity continuum models showed that composition was more important than environment in determining the bulk DOM decay patterns. Changes in DOM composition resulted from the interaction between DOM source and environment. The role of environment was stronger on shaping the bacterial community composition, but the intrinsic nature of the DOM source exerted stronger control on the DOM degradation function.